“We didn’t call it dating”: The disrupted landscape of relationship advice for evangelical Protestant youth - Irby, Courtney, Ann (Critical research on religion, 2013)
Studies of religious meaning-making, especially on young adults, tend to prioritize the views of religious elites and orthodox doctrines. By focusing on the everyday activity of romantic relationships, a topic that has no orthodox position, this article analyzes both how religious elites construct discursive fields of meaning and how laity negotiate this field. Drawing on a study of popular Christian relationship advice books and interviews with young evangelicals, I describe a disrupted landscape produced by evangelical cultural elite discourses that becomes an important context for how young adults imagine and pursue relationships. Yet these efforts, for both evangelical elites and young adults, operate within a broader cultural context of secular “hooking up” practices which serves to create some cohesion among the two groups while also challenging the relevance of the evangelical cultural elite discourses, requiring young adults to engage in their own process of religious meaning-making.